Design and implementation of formal verification tool for combinational circuits using automatic test pattern generation - Tan, Sue Yee. (2010)
Functional Verification or Logical Simulation is an important phase in Digital Design Flow. It is to ensure that the functionality of the design remains the same as the initial desired functionality at any point of time in the whole process, before advancing to the next level. If errors are detected in the early stages, they can be corrected and by doing this, unwanted cost can be reduced.